PENINGKATAN KECERDASAN SPIRITUAL PESERTA DIDIK MELALUI PEMBELAJARAN TAHFIDZ JUZ AMMA - Kamim Tohari; Nafiah, Umi Nahdiyatun (Abtadi : Jurnal Pendidikan Dasar, 2024)
In fact, education does not only produce cognitively proficient students. However, it needs to be balanced with affective aspects to complement the life skills of students in the future. For this reason, this study reviews how the improvement of students’ spiritual intelligence can be obtained by learning tahfidz juz amma through the wahdah method, tasmi’ method, and muraja’ah method. Thus, increasing the spiritual intelligence of students in the form of planting noble morals that can be implemented in everyday life. So that in the future our education can produce knowledgeable people with noble morals based on the values of the Qur’an. This study aims to describe the improvement of students’ spiritual intelligence through the tahfidz juz amma program. In this study, a qualitative approach with descriptive research was applied. In the process of collecting data, researchers used observation methods and direct interviews with teachers and students. The results showed an increase in the spiritual intelligence of students after the implementation of tahfidz juz amma learning through the wahdah method, namely realizing that the ability gained is a gift from Allah which gives birth to an attitude of gratitude. With the tasmi’ method, students have an attitude of caring, cooperation, and honestly in interacting both at school and in the environment. While through the muraja’ah method has a patient and istikamah soul in repeating positive behavior such as reading the Qur’an.